Musical and Musicianly Listening in Intercultural Practice - Östersjö, Stefan (Circuit)

(untitled) (Circuit, musiques contemporaines, 2018)
This paper discusses the function of listening in intercultural musical collaboration, with reference to a number of examples taken from the author’s practice, within the Vietnamese/Swedish group The Six Tones. Through the lens of Pierre Schaeffer’s concepts of musical and musicianly listening, the paper suggests that intercultural exchange takes place in a liminal field between traditions. This demands a particular openness which can be developed by operating musicianly listening, a form of listening which actively seeks to “innovate in the facture of sound objects.”